Joe Biden’s Foreign Policy: What to Expect from the New United States President - Rizky Ihsan (Jurnal Ilmiah Hubungan Internasional, 2022)
Joseph Biden came to the oval office with his wealth of experience in government affairs, including as the chair in the United States Senate Foreign Relations Committee. According to his campaign promises, the upcoming Biden administration’s foreign policy is aimed at improving the US’ international credibility based on liberal values. This article will further examine his political aspirations, based on the speech, campaign promises, and official statements. The argument is that although the US would be likely to embrace liberal values under his administration, international constraints may limit his ability in foreign policy agenda-setting. In managing its relations with China, for example, the US would be more likely to be driven by its interest rather than its values, particularly by continuing the anti-China coalition with its allies in the Indo-Pacific.